Asymmetries in e(+) e(-) -> f(f)over-bar processes at ILC for models with an extra neutral vector boson Z ' - Fortes, E. C. F. S. [UNESP]; Montero, J. C. [UNESP]; Pleitez, V. [UNESP] (Amer Physical Soc, 2010)
Many extensions of the standard model predict the existence of extra neutral vector bosons, generically referred as Z'. This boson may be discovered at the LHC but in this case it will be necessary to study the respective parameters in order to discriminate to which model it belongs to. This is a task for a much clean lepton linear collider as the future International Linear Collinear. In this paper we develop an exemplary study of the capability of several asymmetries on and off Z' peak in discriminating among those extensions with (almost) no ambiguities.